Synthesis and characterization of tungsten nitride (W2N) from WO3 and H2WO4 to be used in the electrode of electrochemical devices. Issue 3 (April 2015) - Villaseca, L.; Moreno, B.; Lorite, I.; Jurado, J.R.; Chinarro, E.
Abstract: Tungsten nitride was synthesized from commercial WO3 and H2 WO4, two precursors with different specific surface areas: 1.0 m 2 /g and 14.7 m 2 /g. The material was prepared by nitridation method by a thermal treatment at 873 K under NH3 flow. The W2 N single phase was obtained with a crystal size of 15 nm and 11 nm, respectively, and with specific surface areas of 7.3 m 2 /g (from WO3 ) and 27.8 m 2 /g (from H2 WO4 ). Both W2 N exhibited high stability after a phosphoric acid attack. The W2 N (WO3 ) powders show a high conductivity with a low activation energy (0.02 eV) measured by Electrochemical Impedance Spectroscopy. Those properties, that is, stability, high electronic conductivity and low activation energy make W2 N a promising candidate to be used in the electrode of electrochemical devices in high corrosive environments.